(untitled) - Gosling, James (Reading, Massachusett, 1996)
Book is volume 2 with Window Toolkit and Applets describes the libraries that you can use to create sophisticated and visually appealing Java applications and applets. In addition, this volume illustrates how you can create embedded programs that can be transported safely across the network. These libraries include java.awt, java.awt.image, java.awt.peer, and java.applet
Keywords: Application program interfaces (Computer software),Java (Computer program language),Giao diện chương trình ứng dụng (Phần mềm máy tính),Java (Ngôn ngữ lập trình máy tính)